Blood Gene Signature for Early Hepatocellular Carcinoma Detection in Patients With Chronic Hepatitis B. Issue 2 (February 2015) - Omar, Haniza; Lim, Chun Ren; Chao, Samuel; Lee, Michelle Mei Lin; Bong, Chin Wei; Ooi, Edie Jian Jiek; Yu, Choon Geok; Tan, Soek Siam; Abu Hassan, Muhammad Radzi; Menon, Jayaram; Muthukaruppan, Raman; Singh, Mandeep; et al.
<x xml:space="preserve">Abstract</x> Purpose: Up to 25% of chronic hepatitis B (CHB) patients eventually develop hepatocellular carcinoma (HCC), a disease with poor prognosis unless detected early. This study identifies a blood-based RNA biomarker panel for early HCC detection in CHB. Materials and Methods: A genome-wide RNA expression study was performed using RNA extracted from blood samples from Malaysian patients (matched HCC, CHB, controls). Genes differentiating HCC from controls were selected for further testing using quantitative real-time polymerase chain reaction. Finally, a 6-gene biomarker panel was identified and characterized using a training set (cohort I=126), and tested against 2 test sets (cohort II=222; cohort III=174). The total number of samples used for each group is: HCC+CHB=143, CHB=211, control=168. Results: Our gene panel displays a consistent trend distinguishing HCC from controls in our test sets, with an area under receiver-operating characteristic curve of 0.9 in cohort III. Our independent test set (cohort III) showed that the gene panel had a sensitivity of 70% with a specificity of 92%. The biomarker profile for HCC was consistently detected in a small subgroup of CHB patients, thus potentially predicting early, preclinical cases of cancer that should be screened more intensively. Conclusion: The biomarkers identified in this study can be used as the basis of a blood-based test for the detection of early HCC in CHB.